2022
DOI: 10.3390/jpm12020144
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Dysfunction in Parkinson’s Disease: Current and Potential Therapeutics

Abstract: Abnormalities in the gastrointestinal (GI) tract of Parkinson’s disease (PD) sufferers were first reported over 200 years ago; however, the extent and role of GI dysfunction in PD disease progression is still unknown. GI dysfunctions, including dysphagia, gastroparesis, and constipation, are amongst the most prevalent non-motor symptoms in PD. These symptoms not only impact patient quality of life, but also complicate disease management. Conventional treatment pathways for GI dysfunctions (i.e., constipation),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 187 publications
(218 reference statements)
0
18
0
Order By: Relevance
“…Unfortunately, there is no effective neuroprotective or disease treatment to stop the progression of PD ( Han et al, 2022 ). Conventional treatments for constipation are also often ineffective for Parkinsonian patients.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there is no effective neuroprotective or disease treatment to stop the progression of PD ( Han et al, 2022 ). Conventional treatments for constipation are also often ineffective for Parkinsonian patients.…”
Section: Introductionmentioning
confidence: 99%
“…Parkinson’s disease (PD) is the second-most common neurodegenerative disease, with a prevalence of more than 1% in the population above 65 years of age which is projected to double by 2030 [ 1 ]. PD patients frequently suffer from motor dysfunctions, including resting tremors, bradykinesia, rigidity, and gait abnormalities, as well as non-motor symptoms such as hyposmia, sleep disorders, depression, cognitive impairment (CI), and gastrointestinal (GI) symptoms [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…PD is a multifactorial disorder resulting from a combination of genetic and environmental factors [ 5 , 6 ]. Over the past decade, it has become increasingly apparent that the gut microbiota and microbial pathogens may contribute to neurodegenerative diseases, either directly or through immune activation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue is dedicated to the optimization of PD treatment and contains several examples of the individualization of treatments with standard PD drugs based on novel sensor and information technology [1][2][3], as well as studies of factors important for making individualized decisions for advanced treatment with continuous dopaminergic drug infusion and deep brain stimulation, DBS [1,[4][5][6]. Several symptoms of PD can be difficult to treat and both the review of gastrointestinal dysfunction and the systematic review of the effect of foot orthoses and shoes in PD address some of those areas [7,8].…”
mentioning
confidence: 99%
“…One of the major problems with the oral administration of levodopa in PD patients in the fluctuation phase is the erratic gastric emptying, which is why infusion therapies have been developed. In the review by Han et al, it is reported that 70-90% of PD patients have gastroparesis [8]. The current resurgence of the interest in understanding the role of the gastrointestinal tract in PD will likely result in new additional treatments for PD in the near future.…”
mentioning
confidence: 99%